The discovery of being & Thomas Aquinas - Cullen, Christopher M.; Harkins, Franklin T. (Catholic University of America Press, 2019)
While there has been agreement among followers of Aquinas that being insofar as it is being (being qua being) is the subject of metaphysics, there is not agreement on how this being qua being is to be understood, nor on how we come to know the being that is the object of metaphysical investigation. The topic of what being is, as the object of the science of metaphysics, and how to account for the "discovery" of the being of metaphysics have emerged as central problems for the contemporary retrieval of Aquinas and for the larger project of post-Leonine Thomism in general. This lack of agreement has hampered the retrieval of Aquinas's metaphysics. The collection of essays within The Discovery of Being and Thomas Aquinas is divided into three major parts: the first set of essays concerns the foundation of metaphysics within Thomism; the second set exemplifies the use of metaphysics in fundamental philosophical issues within Thomism; and the third set employs metaphysics in central theological issues. The Discovery of Being and Thomas Aquinas allows major scholars of the different types of Thomism to engage in a full-scale defense of their position, as well as expanding Thomistic metaphysics to the discipline of theology in important ways